2008
DOI: 10.1073/pnas.0804069105
|View full text |Cite
|
Sign up to set email alerts
|

Two different mitotic checkpoint inhibitors of the anaphase-promoting complex/cyclosome antagonize the action of the activator Cdc20

Abstract: The mitotic checkpoint system ensures the fidelity of chromosome segregation by preventing the completion of mitosis in the presence of any misaligned chromosome. When activated, it blocks the initiation of anaphase by inhibiting the ubiquitin ligase anaphasepromoting complex/cyclosome (APC/C). Little is known about the biochemical mechanisms by which this system inhibits APC/C, except for the existence of a mitotic checkpoint complex (MCC) inhibitor of APC/C composed of the APC/C activator Cdc20 associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 21 publications
2
43
1
Order By: Relevance
“…When such extracts were incubated in the presence of ATP, APC/C was converted to an active form following a lag period. This process was accompanied by the release of inhibitory factors from APC/C and the disassembly of MCC (8,9). We found that the hydrolysis of ATP at the β−γ position was required for both for the activation of APC/C and for the disassembly of MCC (10); this was different from the previously described requirement of checkpoint inactivation for ubiquitylation (11,12), because the latter process involves the cleavage of the α−β bond of ATP (13).…”
contrasting
confidence: 53%
“…When such extracts were incubated in the presence of ATP, APC/C was converted to an active form following a lag period. This process was accompanied by the release of inhibitory factors from APC/C and the disassembly of MCC (8,9). We found that the hydrolysis of ATP at the β−γ position was required for both for the activation of APC/C and for the disassembly of MCC (10); this was different from the previously described requirement of checkpoint inactivation for ubiquitylation (11,12), because the latter process involves the cleavage of the α−β bond of ATP (13).…”
contrasting
confidence: 53%
“…The APC can be inhibited in multiple ways, and complexes of APC together with either Cdc20:C-Mad2, Bub3:BubR1, Bub3:BubR1:Cdc20, MCC, or MCF2 have been found to be inactive (Eytan et al, 2008;Herzog et al, 2009;Kulukian et al, 2009a;Malureanu et al, 2009;Medema, 2009;Sudakin et al, 2001). However, the demand mechanisms for binding the inhibitory complexes to the APC are subject to current research.…”
Section: Apc Inhibitionmentioning
confidence: 99%
“…The MCC may also bind to APC in a kinetochore independent manner to eventually inhibit APC by releasing O-Mad2, forming the stable Bub3:BubR1:Cdc20:APC complex. The recently discovered mitotic checkpoint factor 2 protein (MCF2) is a highly potent APC inhibitor, yet the mechanism of binding to the APC and its regulation is still elusive (Braunstein et al, 2007;Eytan et al, 2008). All complexes inhibiting APC (except of MCF2) rely on the presence of Cdc20:C-Mad2, which requires unattached kinetochores for adequately fast formation.…”
Section: Apc Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations